A retrospective study to evaluate the pattern of spontaneously reported antiretroviral induced adverse drug reactions in a tertiary care hospital - Patil, Swati V.; Pawar, Sudhir R. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: To evaluate the adverse effect profile of spontaneously reported cases of adverse drug reactions due to antiretroviral (ART) drugs in a tertiary care teaching hospital. Methods: A descriptive retrospective study of pattern of ART induced adverse drug reactions (ADRs) spontaneously reported to the Pharmacology department at a tertiary care hospital from January 2011 to December 2016. The details of suspected ADRs including drugs involved, treatment given for ADRs, and the outcome were also documented. These ADRs were analyzed for causality (WHO scale), severity (Hartwig et al. scale), seriousness (ICH E 2A guidelines), preventability (Schumock and Thornton scale) and type based on Edwards and Aronson classification system. Results: Of the 75 cases of ART induced ADRs, reactions were slightly more common in males (52%) and had median age and duration of ART as 36 years and 109 days respectively. Drug induced anemia was the most common presentation followed by cutaneous ADR and zidovudine being the commonest offender. Severity was moderate in 85.3% and causality was probable in 16% and possible in 84% cases. The type reaction was augmented type in 41.3% and not preventable in 76%. Conclusions: Zidovudine is the commonest drug implicated in causing anemia amongst the antiretrovirals. Spontaneous reporting method for antiretroviral pharmacovigilance is insufficient. Targeted spontaneous reporting or cohort event monitoring need to be studied for antiretroviral pharmacovigilance.